Effects of a home-based programme on physiological variables, physical activity, psychological distress and energy intake among undergraduate female students in Iraq - Noori, Jian Abdullah (2016)
The study aimed to evaluate the effect of home-based programme to improve physiological variables, physical activity (PA), psychological distress (PD), and energy intake (EI) among undergraduate female students in Iraq. Besides, aimed to evaluate which variable was the most affected by the home based intervention programme. The participants were Iraqi sedentary undergraduate female students (N=44) who were assigned to two groups consisted of experimental group (N=22) and control group (N=22) respectively. The experimental group received a 12-week home based intervention programme which focuses on (PA and dietary awareness), while the control group were maintaining their usual life. Measurements for all the variables were taken prior to the intervention (pre-test), at week 6 (post-test1), and after 12 weeks (posttest2). Mixed between-within subjects analysis of variance was used to analyse physiological variables and PA, while, two way repeated measure of ANOVA was used to analyse PD and EI. In addition, Cohen's d was used to converting the Eta squared to evaluate which of the variables was more affected by the intervention programme. The results of Mixed between-within subjects analysis of variance shows a statistically significant between the mean test scores in the pre-test, post-test1, and post-test2 measurements of certain physiological variables and PA in the experimental group. The variables were diastolic blood pressure: F (2, 84) =3.507, p<0.05, blood glucose: F (2, 84) =.917, p<0.05, body fat: F (2, 84) =6.246, p<0.05, VO2max: F (2, 84) =57.277, p<0.05, and vital capacity: F (1.654, 69.485) =16.839, p<0.05, and PA: F (2, 84) =731.01, p<0.05) respectively. Two way repeated measures of ANOVA shows a statistically significant between the mean test scores in the pre-test and post-test measurements of participants‟ PD and EI in the experimental group (i.e. total PD: F(1,42)=80.838, p<0.05, depression: F(1,42)=61.105, p<0.05, anxiety: F(1,42)=39.613, p<0.05, stress: F(1,42)=91.271, P<0.05, EI: (F(1,42)=88.332, p<0.05) respectively. Analysis of the post-test2 scores of the experimental and control groups revealed that the difference between the mean scores of the two groups is statistically significant in certain physiological variables: diastolic blood pressure: F(1, 42)=4.948, p<0.05, blood glucose: F(1,42)=8.783, p<0.05, VO2max: F(1, 42)=52.034, p<0.005, vital capacity: F(1, 42)=14.047, p<0.05, and PA F (2, 42)=2260.951, p<0.05 respectively. Meanwhile, the analysis of the post-test scores of the experimental and control groups revealed that the difference between the mean scores of the two groups is statistically significant in PD: total PD: F(1,42)=47.452, p<0.05, depression: F(1, 42)=27.722, p<0.05, anxiety: F(1, 42)= 33.156, p<0.05, stress: F(1, 42)=37,310, <0.05), and EI (F(1, 42)= 40.289, p<0.05) respectively. Finally, the Eta squared showed that certain physiological variables were the more effected by the intervention programme blood cholesterol=18.147 and VO2max=4.467 follow by PA= 18.147, then EI =3.701. While PD =2.774 was the lowest effected by the home based intervention programme. This study provided evidence that home-based intervention programme which focused on PA and dietary awareness had a significant effect on improving physiological variables, PA, PD, and EI. However, to achieve these benefits, exercise and dietary programme need to be carried out regularly as a life routine.